A quality systems study of Foremost Farms Incorporated - Dela Cruz, Alfredo Jojo G.; Du, Michaelangelo T.; Quesada, John Paul L. (Diliman, Quezon City College of Engineering, 1996)
The company under study is Foremost Farms, Incorporated, a semi-integrated feedmill and farm, whose main produce is feedmixes for both piggery and poultry farms. The system under study is the production system of one of its two feedmills. It focuses on the production and quality control sections; how the process works, how quality is applied to the system (process organization, management policies). The study was conducted for the purpose of documenting a traditional industry, and evaluating as to how quality improves the system. It first starts off with a systems audit, identifying the major areas for possible improvement. From this, it identifies lack of statistical control at possible points for garnering improvement. From the survey it goes on to manufacturing process, where the process proper is documented, including the quality system affecting it, the standards or specifications for each quality index inspected, as well as the rate of inspection for each such material. It also takes into account the means of coordination of quality work; the quality policies, objectives and general system in use, as well as the people engaged in quality work within the organization. Quality information systems are also present; what quality measures are important, what programs are present, the costs for doing or not doing quality work. Based on the documentation gathered, two major and two minor possible improvement areas are gathered. The two major ones are the lack of sufficient data for process control and the lack of systems and procedures for documenting and analyzing control data. The two minor ones are with regard to the lack of homogeneity in the mixing operation of the feedmill and the possibility of increased inspection.
Out of the problem areas, it concludes with recommendations as to possible means of improving the system, as well as the time table of such recommendations. Based on the analysis of the possible improvement areas, one recommendation points to the possible increase of the number of nutrient data collected. Once a sufficient amount of data has been gathered, statistical tools such as control charts can be implemented to determine the state of stability of the mixer operation and eventually solve the problem of a non-homogenous feed mixture. Based on the cost-benefit analysis, present set ups would be most economical in taking only two samples per day for calcium and phosphorus tests alone, in the short term. However, to enhance its reputation as quality feedmill, as well as to ensure highly satisfactory products, the two samples per batch run is required for the long term. Another recommendation focuses on the systems and procedures of quality information being used. In this manner, forms for quality documentation are administered in the raw materials, finished goods and the dousing operations, with some accompanying systems and procedures of the production process to fit the use of forms. Furthermore, other recommended areas for improvement are the making of the raw material sacks for determining how long stocks are in storage to avoid quality degradation of neglected stocks as well as a "5s" program for proper plant upkeep. Overall, Foremost Farms proves to be a major player in the field, and will continue to do so given the highly qualified department heads and supervisors. In this manner, it is the groups aspiration that a study contribute to the development of a better flow of operations, and help in producing a more "lean and mean" agricultural sector.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Foremost Farms Incorporated; Poultry industry; Quality control